2017
DOI: 10.3727/152599517x14942648527527
|View full text |Cite
|
Sign up to set email alerts
|

Volunteers with Disabilities at the London 2012 Olympic And Paralympic Games: Who, Why, and Will They Do It Again?

Abstract: People with disabilities are often the recipients of volunteer services but are rarely considered as a potential volunteer resource, such as in sport events where volunteers are an essential component of major sport event operation and legacy potential. For London's 2012 Olympic and Paralympic Games, there was a determined effort by the Organizing Committee to recruit people with disabilities to be Games Makers (i.e., volunteers). This exploratory research investigated 786 London 2012 volunteers who self-ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 48 publications
2
13
0
1
Order By: Relevance
“…The EFA results showed that the KMO index obtained a high value, above 0.90 (Visauta et al, 2005). Regarding the extracted variance it was observed that the three factors extracted allowed an explanation of 61.17% of the variance, results that are similar to those obtained in previous studies that have used this scale (Dickson et al, 2013(Dickson et al, , 2014(Dickson et al, , 2015(Dickson et al, , 2017Khoo & Engerholm, 2007Lockstone-Binney et al, 2015) and higher than the results obtained by Farrell et al (1998). The reliability values using Cronbach's alpha index were higher than the minimum of 0.7 established by Nunnally and Bernstein (1994).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The EFA results showed that the KMO index obtained a high value, above 0.90 (Visauta et al, 2005). Regarding the extracted variance it was observed that the three factors extracted allowed an explanation of 61.17% of the variance, results that are similar to those obtained in previous studies that have used this scale (Dickson et al, 2013(Dickson et al, , 2014(Dickson et al, , 2015(Dickson et al, , 2017Khoo & Engerholm, 2007Lockstone-Binney et al, 2015) and higher than the results obtained by Farrell et al (1998). The reliability values using Cronbach's alpha index were higher than the minimum of 0.7 established by Nunnally and Bernstein (1994).…”
Section: Discussionsupporting
confidence: 83%
“…Values in the load factors greater than 0.30 are indicative that a high percentage of the sample variance is explained by the given factor (Child, 2006). Contrary to this study, previous research showed that the Purposive factor was the most representative (Dickson et al, 2017;Farrell et al, 1998;Khoo & Engelhorm, 2007;. The Commitment/External Traditions showed similar load factors as reported in previous studies (Johnston et al, 1999;Lockstone-Binney et al, 2015).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Importantly at this micro-level, researchers have been more successful at increasing the voices and experiences of disabled people. Disabled people's interaction with multi-level barriers that prevent social inclusion is a common theme, whether in participation (Darcy et al, 2017;Darcy & Dowse, 2013;Ives et al, 2021;Sotiriadou & Wicker, 2014), spectatorship (Brown, 2020;García et al, 2017;Paramio-Salcines et al, 2018;Penfold & Kitchin, 2020), or employment in sport (Dickson et al, 2017;Kappelides & Spoor, 2019;Wright & Cunningham, 2017). Kappelides and Spoor (2019) examined the experiences of disabled people who volunteered in sport.…”
Section: Disability Sport Managementmentioning
confidence: 99%
“…Az inkluzív önkéntesség a fogyatékossággal élő személyek részvételét erősíti a különféle közösségépítő tevékenységekben (Marková 2018), melyek köre diverz és sokszínű területet ölel fel: a mega sportesemények világától kezdve, a munkaerő-piaci beilleszkedést támogató tevékenységeken keresztül, az inklúziót segítő szolgáltatásokig (Hall -Wilton 2011;Dickson et al 2017).…”
unclassified